Closure of large wounds using rubber bands in rabbits - Magalhães,Maria Angélica Baron (2015)
OBJECTIVE: to verify the effectiveness of the rubber elastic band in the treatment of large wounds of the body wall of rabbits by means of traction of its edges. METHODS: we studied 30 New Zealand rabbits, divided into three groups (n=10): Group 1- healing by secondary intention; Group 2- removal and eutopic repositioning of skin as full thickness skin graft; Group 3- Approximation of wound edges with elastic rubber band. In all animals, we removed a segment of the back skin and subcutaneous tissue down to the fascia, in accordance with an acrylic mold of 8cm long by 12cm wide. All animals were observed for 21 days. RESULTS: two animals of groups 1 and 2 had wound abscess. In Group 2, there was partial or total graft loss in 90% of animals. The complete closure of the wounds was observed in four animals of Group 1, six of Group 2 and eight of Group 3. There was no difference between the scar resistance values of groups 2 and 3, which were higher than those in Group 1. The scars of the three groups were characterized by the presence of mature connective tissue mixed with blood vessels and inflammatory infiltration, predominantly polymorphonuclear. CONCLUSION: the tensile strength of the wound edges with rubber elastic band is as efficient as the skin graft to treat rabbits' large body wounds.